LEARNED RESOURCEFULNESS, RATIONAL DRUG USE, AND ATTITUDE OF PATIENT RIGHTS USING IN PREGNANT WOMEN: PREGNANT, LEARNED RESOURCEFULNESS, RATIONAL DRUG USE, PATIENT RIGHTS - MALAK AKGÜN, Bahanur (Göbeklitepe Medical Science Journal, 2024)
It was aimed to determine the learned resourcefulness, rational drug use and patient rights knowledge levels of pregnant women. The study was carried out in accordance with the qualitative research design and was supported by quantitative data. 16 pregnant women participated in the study. Data were collected using Introductory Information Form, Rosenbaum’s Learned Resourcefulness Scale, Rational Drug Use Scale, and Patient Rights Using Attitude Scale. The questions prepared to the views and thoughts of pregnant women about pregnancy processes. An important factor that determines whether pregnant women are satisfied with the service provided despite receiving equal service delivery is the limited availability of hospital facilities. These limited opportunities include factors such as personnel and equipment. It has been understood that their satisfaction with these services (such as receiving attention, getting adequate and understandable answers) varies according to their level of learned resourcefulness and knowledge of patient rights. Due to limited opportunities, sometimes the lack of respect for the privacy and values ​​of pregnant women affected their satisfaction with health services and caused them to have an opinion that the health personnel were indifferent to them. Pregnant women are very compliant in complying with the recommendations given by the health personnel; in general, emotion-focused coping with stress is applied, very few of them are able to cope with problem-focused; It is understood that widespread negative information about the harm of smoking on health is internalized and cigarette consumption is terminated during pregnancy. It is recommended that pregnant women benefit more effectively from patient rights by establishing empowerment programs that enable them to have sufficient knowledge about rational drug use and increase their level of learned resourcefulness.